2018
DOI: 10.15294/ujph.v7i1.16705
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Factors on Performance of Tuberculosis Program Officers at Community Health Clinic in Increasing the Finding of New AFB Smear-Positive Cases

Abstract: Semarang regency had CDR issues under the national target. The activity of new cases finding determine the success of the tuberculosis eradication programs, so the process of find new AFB smear-positive cases by officers is crucial. The purpose of this study was to determine factors related to the performance of tuberculosis officers at the Health Center in increasing the findingof New AFB smear-positive cases (case study in Semarang regency). This type of research is observational analytic, with the cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…So, it can be concluded that there is a relationship between workload and the performance of tuberculosis program officer in the CDR. The results of this study are in line with the research conducted by Latifah et al (2018) showing that there is a relationship between workload (dual-task) and the performance of TB program officers in community health center in increasing the discovery of new AFB smear-positive cases in Semarang Regency. The research results show a p-value of 0.014 which means that there is indeed a relationship between workload and performance.…”
Section: Resultssupporting
confidence: 89%
“…So, it can be concluded that there is a relationship between workload and the performance of tuberculosis program officer in the CDR. The results of this study are in line with the research conducted by Latifah et al (2018) showing that there is a relationship between workload (dual-task) and the performance of TB program officers in community health center in increasing the discovery of new AFB smear-positive cases in Semarang Regency. The research results show a p-value of 0.014 which means that there is indeed a relationship between workload and performance.…”
Section: Resultssupporting
confidence: 89%
“…Training for executor surveillance Tuberculosis is done To increase officers' knowledge, attitudes, and skills to increase competence and performance (11). Several power surveillance Tuberculosis at the health center experience double job constraints, influencing performance in activity surveillance (12). Double jobs are caused by mutated employees and structured organizations that do not need to be more apparent.…”
Section: Inputmentioning
confidence: 99%
“…Several significant efforts need to be made to achieve this target, including community empowerment to early detection and improving the quality of DOTS in all health facilities (Latifah et al, 2018;Rahayu et al, 2015). Community empowerment efforts are carried out to increase public awareness of TB disease, its prevention and treatment so that the community can be actively involved in case finding (Rita et al, 2019;Kartika, 2015).…”
Section: Introductionmentioning
confidence: 99%